Employment of youth in Malaysia during covid-19 pandemic - Eng, Keng Seng; Lim, Fui Yee Beatrice; Nga, Lay Hui Janice (Faculty of Business, Economics and Accountancy, 2021)
The unemployment of youth is an important issue which always highlighted and reviewed by the Malaysian government. Although the national unemployment rate is low every year, the youth unemployment rate was recorded at a two-digit figure every year. The COVID-19 pandemic had further increased the youth unemployment recently. The Malaysian government had provided initiatives and incentives under economic plans and packages such as PRIHATIN, PENJANA, National Budget 2021 and PEMULIH, to assist the youths in tackling youth unemployment during the pandemic crisis. There are initiatives can be taken by youths to get themselves employed such as learning new skills to increase employability, engage in place and train programme, become entrepreneurs, engage in e-commerce to become self-employed during the pandemic crisis.